Identification of DHA-23, a novel plasmid-mediated and inducible AmpC beta-lactamase from Enterobacteriaceae in Northern Taiwan - Hsieh, Wen-Shyang; Wang, Nai-Yu; Feng, Jou-An; Weng, Li-Chuan; Wu, Hsueh-Hsia (Frontiers in Microbiology, 2015)
Objectives: AmpC β-lactamases are classified as Amber Class C and Bush Group 1. AmpC β-lactamases can hydrolyze broad and extended-spectrum cephalosporins, and are not inhibited by β-lactamase inhibitors such as clavulanic acid. This study was conducted to identify DHA-23, a novel plasmid-mediated and inducible AmpC β-lactamase obtained from Enterobacteriaceae. Methods: A total of 210 carbapenem-resistant Enterobacteriaceae isolates were collected from a medical center (comprising two branches) in Northern Taiwan during 2009–2012. AmpC β-lactamase genes were analyzed through a polymerase chain reaction using plasmid DNA templates and gene sequencing. The genetic relationships of the isolates were typed using pulsed-field gel electrophoresis following the digestion of intact genomic DNA by using XbaI. Results: Three enterobacterial isolates (one Escherichia coli and two Klebsiella pneumoniae) were obtained from three hospitalized patients. All three isolates were resistant or intermediately susceptible to all β-lactams, and exhibited reduced susceptibility to carbapenems. These three isolates expressed a novel AmpC β-lactamase, designated DHA-23, approved by the curators of the Lahey website. DHA-23 differs from DHA-1 and DHA-6 by one amino acid substitution (Ser245Ala), exhibiting three amino acid changes compared with DHA-7 and DHA-Morganella morganii; three amino acid changes compared with DHA-3; four amino acid changes compared with DHA-5; and eight amino acid changes compared with DHA-2 (>97% identity). This AmpC β-lactamase is inducible using a system involving ampR. Conclusion: This is the first report to address DHA-23, a novel AmpC β-lactamase. DHA-type β-lactamases are continuous threat in Taiwan.